Classification of Nouns Based on the Reading of a Poem: Analysis of Didactic Sequences Applied in the High School Classroom - Poggio, Anabella; Funes, María Soledad (Huarte de San Juan. Filología y Didáctica de la Lengua, 2020)
This paper shows the results of applying a didactic sequence in the first year of adults’ secondary schools in Buenos Aires city. The activities involved were crafted using the perspective of Cognitive-Prototypical Approach (CPA) (Langacker, 1987, 1991; Lakoff, 1987), which states Grammar is a system of tendencies that reflects a certain society’s worldview. We start from the hypothesis that the discursive approach offered by the CPA overcomes the limitations of operating at sentence level, and therefore allows students a better understanding of grammar categories than the one reached through out-of-context methods. Through the sequence analysis, we conclude that activities set from a discursive approach contributed to enhance the understanding of the grammar topic and the text interpretation.